Analisis Perkembangan Emosional Anak Saat Kegiatan Drumband di TK Hang Tuah Perwakilan Bengkulu - Diya, Diya; Aprilia, Shinta; Nadillah, Welia (UIN Fatmawati Sukarno Bengkulu, 2025)
This research aims to determine the internal control system for investment funds at the Bengkulu City Branch Family Takaful Insurance. To find out the investment fund control system in depth and comprehensively, the researcher used a qualitative descriptive method which is useful for providing information, facts, and data on the internal control system of investment funds at the Bengkulu City Branch Family Takaful Insurance. Then the data is described, analyzed, and discussed to answer these problems. From the results of this research, it was found that in the internal control system for investment funds at the Bengkulu City Branch Family Takaful Insurance, there were still some customers who did not accept the profits from the investments made because they were considered to be very low. The Bengkulu City Branch of Family Takaful Insurance is also still experiencing problems with data filing, sometimes the filing information provided by agents does not comply with the structure that has been implemented. However, overall the internal control system for investment funds at the Bengkulu City Branch Family Takaful Insurance is quite good.